PERAN STRATEGIS PENDIDIKAN DALAM MEMPERKUAT INTEGRASI GREEN-BLUE, EKONOMI DIGITAL DAN KREATIF UNTUK PEMBANGUNAN BERKELANJUTAN - Hadiyani, Rahmilia; Azis, Darlis; Khairul, Muhammad; Angkasa, Muhammad Akbar (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Economic education has a strategic role in strengthening the integration of the Green-Blue Economy (GBE), Digital Economy (ED), and Creative Economy (CE) sectors as pillars of sustainable development in Indonesia. This research aims to analyze the structural barriers in the trisectoral integration and formulate a relevant transformative education model. Using the Systematic Literature Review (SLR) method based on the PRISMA protocol, 68 selected documents (2018-2024) were thematically analyzed using the Braun & Clarke approach. The results showed three main findings: (1) significant cross-sector competency gaps, (2) low adoption of integrative curricula in higher and vocational education, and (3) evidence of the effectiveness of project-based education approaches in improving HR competitiveness. The